2013
DOI: 10.1107/s0907444913019379
|View full text |Cite
|
Sign up to set email alerts
|

Structure of the Sgt2 dimerization domain complexed with the Get5 UBL domain involved in the targeting of tail-anchored membrane proteins to the endoplasmic reticulum

Abstract: The insertion of tail-anchored membrane (TA) proteins into the appropriate membrane is a post-translational event that requires stabilization of the transmembrane domain and targeting to the proper destination. Sgt2, a small glutamine-rich tetratricopeptide-repeat protein, is a heat-shock protein cognate (HSC) co-chaperone that preferentially binds endoplasmic reticulum-destined TA proteins and directs them to the GET pathway via Get4 and Get5. The N-terminal domain of Sgt2 seems to exert dual functions. It me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 52 publications
0
12
0
Order By: Relevance
“…The very recent past saw a number of simultaneous publications from different research groups providing new insights into SGTA, its relationship with the BAG6 holdase complex and the equivalent yeast system including [10], [18], [22], [24], [25]. As a result of the concurrent timing most of these studies did not have the benefit of knowing about each other during their preparation and hence there is some overlap.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The very recent past saw a number of simultaneous publications from different research groups providing new insights into SGTA, its relationship with the BAG6 holdase complex and the equivalent yeast system including [10], [18], [22], [24], [25]. As a result of the concurrent timing most of these studies did not have the benefit of knowing about each other during their preparation and hence there is some overlap.…”
Section: Discussionmentioning
confidence: 99%
“…Our group solved the solution structure of the Sgt2 dimerisation domain (Sgt2_NT) which forms a novel helical fold [18]. Various other Sgt2/SGTA structures have also been added to the literature, namely NMR solution [22] and X-ray crystal [25] structures of partial forms of Sgt2_NT in the context of its complex with Get5, and SGTA_NT [22] encompassing the first two or three out of the four helices in each monomer that we present here. These structures largely agree with each other, differing predominantly in the C-terminal regions remote from the UBL binding interface, apparently as a result of the use of truncated constructs of SGTA and Sgt2 in the latter studies.…”
Section: Discussionmentioning
confidence: 99%
“…15,16 The BAG6 complex facilitates the ER-associated degradation of certain aberrant membrane proteins and the ubiquitination and degradation of mislocalized membrane and secretory proteins that fail to reach the ER and remain in the cytosol. 17,18 However, it was also showed that GdX interacted with Arp2/3 in membrane ruffles and lamellipodia and eventually influenced insulin-induced Akt plasma membrane translocation. 10 Interestingly, we previously observed GdX associated with STAT3 to mediate its dephosphorylation.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the TPR domain of Sgt1 (suppressor of G2 allele SKP1, not to be confused with Sgt2 and SgtA) has also been shown to homodimerize, although structural detail of this is also lacking (Nyarko et al, 2007). In contrast, Sgt2 and SgtA (small glutamine-rich TPR-containing protein) have an N-terminal dimerization domain (Tung et al, 2013;Liou & Wang, 2005;Chartron et al, 2012;Tobaben et al, 2003), as does the orthologue from Caenorhabditis elegans (Worrall et al, 2008), for which structural details of the dimerization have recently been reported (Chartron et al, 2012). These differ from those of Tah1 and suggest that many different mechanisms of dimerization may be employed by TPR domain-containing proteins.…”
Section: Discussionmentioning
confidence: 99%